Asymptomatic Severe Vagal and Sympathetic Cardiac Denervation in Holmes-Adie’s Syndrome - B. Estañol; R. C. Callejas-Rojas; S. Cortés; R. Martínez-Memije; O. Infante-Vázquez; G. Delgado-García (Case Reports in Neurological Medicine)
A 40-year-old woman was found to have bilateral Adie’s pupils and generalized muscle stretch areflexia. She did not have orthostatic hypotension but, in an ECG strip in the office, she appeared to have an almost fixed heart rate. We thus studied the heart rate variability (HRV) and the systolic blood pressure variability (SBPV) in supine and standing position and also during rhythmic breathing. We found a decreased HRV in the time domain with very low standard deviation in supine and standing position and during rhythmic breathing. HRV in the frequency domain was low with a decrease in the absolute power of HF and LF and a decrease in the sympathovagal balance in supine and standing positions. SBPV in the time and frequency domains was found to be normal. This patient with Holmes-Adie syndrome had an asymptomatic severe loss of HRV and a preserved SBPV. The global decrease in the HRV in the time and frequency domains indicated that she had both vagal and sympathetic cardiac denervation, whereas the preserved SBPV suggested normal innervation of the blood vessels.